1992
DOI: 10.1029/91jc02821
|View full text |Cite
|
Sign up to set email alerts
|

The sizes, frequencies, and freeboards of East Greenland icebergs observed using ship radar and sextant

Abstract: The Scoresby Sund fjord system, East Greenland, contains the most productive fast‐flowing outlet glaciers draining east from the Greenland Ice Sheet, calving 18 km3 a−1 of icebergs. The sizes, frequencies, and freeboards of 1900 icebergs were measured from F.S. Polarstern, using ship X‐band radar and sextant. Radar beam spreading exaggerates iceberg width by 60 m per nautical mile of range beyond the first mile. Data sets on iceberg size (e.g., that collated for Antarctic icebergs) collected using ship radars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 18 publications
3
83
0
Order By: Relevance
“…Parasound and 3.5 kHz acoustic measurements recorded seabed irregularities up to 10 m in height (from berm crest to the base of the trough) and widths of a few metres to 20 m or more (Dowdeswell et al, 1993). These irregularities are inferred to be scours because i) they are similar in morphology to those seen on 3.5 kHz records from the Labrador Shelf and Barents Sea (Josenhans et al, 1986;Solheim et al, 1988); ii) Dowdeswell et al (1992Dowdeswell et al ( , 1993 observed a large number of ice-bergs with keels deeper than the measured water depths; and iii) the dimensions of these seabed irregularities are consistent with previous scour descriptions in terms of size and berm/trough morphology. Given sedimentation rates in Scoresby Sund over the last 10 ka are on the order of 0.2-0.3 mm yr -1 (Marienfield, 1992a), it is likely that, as well as modern scours, relict scours dating back to the Late Wiechselian are probably also present on the modern sea floor, and even older scours (Mid and Early Weichselian) are likely to exist throughout the sedimentary sequence where it has not been eroded by later glaciations (Dowdeswell et al, 1993).…”
Section: Seafloor Scouring By Iceberg Keelsmentioning
confidence: 85%
See 4 more Smart Citations
“…Parasound and 3.5 kHz acoustic measurements recorded seabed irregularities up to 10 m in height (from berm crest to the base of the trough) and widths of a few metres to 20 m or more (Dowdeswell et al, 1993). These irregularities are inferred to be scours because i) they are similar in morphology to those seen on 3.5 kHz records from the Labrador Shelf and Barents Sea (Josenhans et al, 1986;Solheim et al, 1988); ii) Dowdeswell et al (1992Dowdeswell et al ( , 1993 observed a large number of ice-bergs with keels deeper than the measured water depths; and iii) the dimensions of these seabed irregularities are consistent with previous scour descriptions in terms of size and berm/trough morphology. Given sedimentation rates in Scoresby Sund over the last 10 ka are on the order of 0.2-0.3 mm yr -1 (Marienfield, 1992a), it is likely that, as well as modern scours, relict scours dating back to the Late Wiechselian are probably also present on the modern sea floor, and even older scours (Mid and Early Weichselian) are likely to exist throughout the sedimentary sequence where it has not been eroded by later glaciations (Dowdeswell et al, 1993).…”
Section: Seafloor Scouring By Iceberg Keelsmentioning
confidence: 85%
“…More recent estimates from the period 2000-2010 measured an ice flux at the grounding-line of Daugaard-Jensen Gletscher of 25 km 3 yr -1 , although a daily submarine melt rate of about 2.5 m per day means that calving may account for only 4 km 3 yr -1 (Enderlin and Howat, 2013). These two outlet glaciers produce tabular icebergs between 100 m and 2.5 km in width, and up to 600 m in thickness (Dowdeswell et al, 1992); by contrast smaller tidewater glaciers tend to produce smaller icebergs of irregular shape (Dowdeswell et al, 1994a,b). The net drift of icebergs is to-wards the mouth of the fjord system where icebergs leave the outer fjord on its southern side (Dowdeswell et al, 1993).…”
Section: Icebergsmentioning
confidence: 99%
See 3 more Smart Citations